1990
DOI: 10.1111/j.1398-9995.1990.tb00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intestinal anaphylactic reactions in sensitized mice challenged with untreated bovine milk and homogenized bovine milk

Abstract: Outbred NMRI mice were sensitized for high IgE production either by subcutaneous injections of low doses of untreated bovine milk or homogenized bovine milk in combination with intraperitoneal injections of Freund's Complete Adjuvant or by oral administration of untreated or homogenized bovine milk without adjuvant. When analysed in murine passive cutaneous anaphylaxis test both types of milk resulted in production of reaginic antibodies against bovine milk proteins when given subcutaneously. When given orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Poulsen et al [24] demonstrated very early on that intestinal anaphylaxis after an oral challenge is associated with the release of histamine and other mediators leading to acute systemic symptoms. We thus performed a histamine provocation test, as already described by Li et al [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Poulsen et al [24] demonstrated very early on that intestinal anaphylaxis after an oral challenge is associated with the release of histamine and other mediators leading to acute systemic symptoms. We thus performed a histamine provocation test, as already described by Li et al [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Allergy‐related health effects associated with homogenization have been discussed in the context of milk allergy (reviewed in [15]). In animal models there is some evidence that homogenization favours milk allergy [16], but these findings have not been confirmed in clinical studies [15]. No studies exist so far examining a potential effect of homogenization on the development of asthma or allergic diseases other than milk allergy.…”
Section: Processing Of Cow's Milkmentioning
confidence: 99%
“…Homogenization of cow’s milk is also a factor which improves the induction of sensitization in a murine model [29]. …”
Section: Discussionmentioning
confidence: 99%